Variables Affecting Success in Economic Education: Preliminary Findings from a New Data Base - Baumöl, William J.; Highsmith, Robert J. (American Economic Review, 1988)
The output of the considerable effort expended on economic education in the schools of the United States is, of course, the resulting contribution to the students' degree of understanding of the workings of our economy and their pertinent reasoning ability. A comprehensive survey questioning both teachers and students, whose first phase has now been completed, permits a more extensive description of what has been achieved, of the means that have been used in the process and of the resources available for the purpose. Perhaps even more important, it makes possible an empirical analysis of the relationship between the inputs and the outputs-the methods and resources used and the achievements of the students. This article describes some of the main results obtained from a first analysis of these data. Among the major results to date that emerge from this study are the following conclusions: 1) Students who receive formal training in economics at the senior level in high school, consisting of a minimum of three hours per week, understand some economic topics quite well but have major gaps in their understanding of others. 2) Students share with their teachers many of the same goals for studying economics, but students believe that these goals are less important than teachers believe them to be. 3) Most economics students have not had any experience in studying economics prior to the senior level course. 4) Economics students believe that economics helps them to think more systematically about some kinds of issues they face, but not others. 5) Student attitudes toward their economics courses vary considerably, with 23 percent describing themselves as liking economics a lot, 42 percent as liking it a little, 16 percent as unsure, 7 percent as disliking it a little, and 6 percent as disliking it a lot. 6) Senior students receiving formal training in economics constitute a fairly representative group in terms of Scholastic Aptitude Test scores but not in terms of the educational achievements of their parents. 7) Teachers giving instruction in economics at the high school level vary widely in the amount of their college training in economics and in their experience in teaching it. 8) The gender and ethnic backgrounds of economics teachers differ from those of economics students. 9) The topics in economics most frequently included by economics teachers in their courses were supply and demand, how market and prices work, and monetary and fiscal policy. Topics most neglected include balance of payments, how to interpret economic data, and measurement concepts. 10) The teachers felt that the instructional materials most helpful to them were newspapers, textbooks, and graphs and charts. *Professor of Economics, Princeton University, Princeton, NJ 08544 and New York University; and Director of Research, Joint Council on Economic Education, 432 Park Avenue South, New York, NY 10016, respectively. We are extremely grateful to the J. Howard Pew Freedom Trust, Inc. whose generous grant to the Joint Council on Economic Education and Princeton University made possible the research underlying this paper and the creation of the data base on economic education. The basic ideas for this work originated in the Joint Council, which provided supervision throughout the project. The data collection was carried out promptly and competently by Audrey McDonald. Invaluable suggestions and comments were provided by an advisory committee composed of Wil11am Becker, Indiana University; Marilyn Kourilsky, UCLA; Charles Plott, California Institute of Technology; and Sherwin Rosen, University of Chicago.